The Arabidopsis thylakoid chloride channel AtCLCe functions in chloride homeostasis and regulation of photosynthetic electron transport - Andrei eHerdean; Hugues eNziengui; Otto eZsiros; Katalin eSolymosi; Gyözö eGarab; Björn eLundin; Cornelia eSpetea (Frontiers in Plant Science, 2016)
Chloride ions can be translocated across cell membranes through Cl− channels or Cl−/H+ exchangers. The thylakoid-located member of the Cl− channel CLC family in Arabidopsis thaliana (AtCLCe) was hypothesized to play a role in photosynthetic regulation based on the initial photosynthetic characterization of clce mutant lines. The reduced nitrate content of Arabidopsis clce mutants suggested a role in regulation of plant nitrate homeostasis. In this study, we aimed to further investigate the role of AtCLCe in the regulation of ion homeostasis and photosynthetic processes in the thylakoid membrane. We report that the size and composition of proton motive force were mildly altered in two independent Arabidopsis clce mutant lines. Most pronounced effects in the clce mutants were observed on the photosynthetic electron transport of dark-adapted plants, based on the altered shape and associated parameters of the polyphasic OJIP kinetics of chlorophyll a fluorescence induction. Other alterations were found in the kinetics of state transition and in the macro-organisation of photosystem II supercomplexes, as indicated by circular dichroism measurements. Pre-treatment with KCl but not with KNO3 restored the wild-type photosynthetic phenotype. Analyses by transmission electron microscopy revealed a bow-like arrangement of the thylakoid network and a large thylakoid-free stromal region in chloroplast sections from the dark-adapted clce plants. Based on these data, we propose that AtCLCe functions in Cl− homeostasis after transition from light to dark, which affects chloroplast ultrastructure and regulation of photosynthetic electron transport.